Regulation of amphiregulin gene expression by β-catenin signaling in human hepatocellular carcinoma cells: a novel crosstalk between FGF19 and the EGFR system. - Maria U Latasa; Fabiana Salis; Raquel Urtasun; Oihane Garcia-Irigoyen; Maria Elizalde; Iker Uriarte; Monica Santamaria; Francesco Feo; Rosa M Pascale; Jesús Prieto; Carmen Berasain; Matías A Avila (PLoS ONE, 2012)
Hepatocellular carcinoma (HCC) is the most prevalent liver tumor and a deadly disease with limited therapeutic options. Dysregulation of cell signaling pathways is a common denominator in tumorigenesis, including hepatocarcinogenesis. The epidermal growth factor receptor (EGFR) signaling system is commonly activated in HCC, and is currently being evaluated as a therapeutic target in combination therapies. We and others have identified a central role for the EGFR ligand amphiregulin (AR) in the proliferation, survival and drug resistance of HCC cells. AR expression is frequently up-regulated in HCC tissues and cells through mechanisms not completely known. Here we identify the β-catenin signaling pathway as a novel mechanism leading to transcriptional activation of the AR gene in human HCC cells. Activation of β-catenin signaling, or expression of the T41A β-catenin active mutant, led to the induction of AR expression involving three specific β-catenin-Tcf responsive elements in its proximal promoter. We demonstrate that HCC cells expressing the T41A β-catenin active mutant show enhanced proliferation that is dependent in part on AR expression and EGFR signaling. We also demonstrate here a novel cross-talk of the EGFR system with fibroblast growth factor 19 (FGF19). FGF19 is a recently identified driver gene in hepatocarcinogenesis and an activator of β-catenin signaling in HCC and colon cancer cells. We show that FGF19 induced AR gene expression through the β-catenin pathway in human HCC cells. Importantly, AR up-regulation and EGFR signaling participated in the induction of cyclin D1 and cell proliferation elicited by FGF19. Finally, we demonstrate a positive correlation between FGF19 and AR expression in human HCC tissues, therefore supporting in clinical samples our experimental observations. These findings identify the AR/EGFR system as a key mediator of FGF19 responses in HCC cells involving β-catenin signaling, and suggest that combined targeting of FGF19 and AR/EGFR may enhance therapeutic efficacy.